New public management and the reform of French public hospitals. Issue 3 (2nd July 2013) - Simonet, Daniel
Abstract : New public management (NPM) is not only an Anglo‐Saxon debate but also a French one, with some of its elements constituting structural components of the French state apparatus. How did it make its way into French hospitals? What core mechanism was at the center of NPM implementation in hospitals? We discuss the redisorganization of the health system under NPM, as it attempted to reassert the central government's power over regions and how it alienated the medical profession. The paper highlights inherent contradictions and other false promises within NPM. It was unable to contained cost, could no enhance accountability or increase civil participation. We then investigate post‐NPM reforms in French healthcare. Copyright © 2013 John Wiley & Sons, Ltd.